Criminalization of Homosexuality in Islamic Criminal Jurisprudence with a Critical Approach to Article 237 of the Islamic Penal - MARYAM AZIZIYAN FARSANI; SAIED MOLAVI VARDANJANI (مطالعات فقه و حقوق اسلامی, 2017)
In Article 237 of the Islamic Penal Code 2013, homosexuality or emotional and sexual trend between two males or two females means same-sex sexual or sexual behavior of two males or two females which is criminalized in the form of Sodomy, Tafkhiz, Lesbianism, Taghbil, Molameseh and other sexual pleasures. But it is not obviously used in the Islamic Criminal Law, though in the "Makasib Moharamah" it is matched with the words "Ta'anos"(femininity) and "Tazakor" (masculinity) that mean sodomy and lesbianism or interest in these two relationships. Of course lack of clarification of issue in jurisprudence of discretionary punishment (Taazir) and prescribed punishment (Had), along with strong prohibition documentation available in the sources of Islamic law (i.e. book, tradition, reason and consensus) does not mean denying being criminal of committed conduct of issue But also it seems as sequence of relying to the ruling and thematic alliance theory of natural general and its subjects, as well as the current principle of "discretionary punishment for all illegal actions" , the prohibition of femininity and masculinity has been mentioned in civil jurisprudence